Implementasi Reformasi Birokrasi - Ahmad Rifa'i; Albetris Albetris (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to describe the implementation model of bureaucratic reform that has been carried out, both in Indonesia and several other countries. Provide a comprehensive understanding of the importance of bureaucratic reform. The research method used is a library research method from various sources related to bureaucratic reform. The results of this literature review illustrate that bureaucratic reforms that have been carried out in several countries are generally related to two dimensions, namely the organizational dimension and the apparatus human resource dimension. In the context of implementing the implementation of bureaucratic reform at the Provincial Bawaslu and Regency/City Bawaslu, it is necessary to immediately make and determine the Decree of the Bureaucratic Reform Team, make and determine the Decree of Role Models and Agents of Change of Bureaucratic Reform which includes 8 areas of change, preparation of an implementation action plan. bureaucratic reform, filling out the bureaucratic reform evaluation worksheet, monitoring and evaluating the implementation of bureaucratic reform every month.